2006
DOI: 10.1130/g22784a.1
|View full text |Cite
|
Sign up to set email alerts
|

Magnitudes and source areas of large prehistoric northern Alpine earthquakes revealed by slope failures in lakes

Abstract: Figure 1. A: Location map showing tectonic units and epicenters of instrumentally (gray dots) and historically (M Ն 5.5, red dots) recorded earthquakes (Fä h et al., 2003). Box in center locates study area with Lake Zurich and Lake Lucerne. Profile line and swath (dashed lines) indicate Alpine profile and maximum earthquakeprojection distance in B. NAF is North Alpine nappe front. B: Present-day uplift rates (after Schlatter and Marti, 2002) along Alpine tectonic profile (after Pfiffner and Heitzmann, 1997; Pf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
134
0
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 152 publications
(137 citation statements)
references
References 18 publications
1
134
0
2
Order By: Relevance
“…The age model for the lower part of the core was constrained using two radiocarbon dates published in Thevenon and Anselmetti (2007), and two new radiocarbon dates (ETH-37378 and ETH-37379) also carried out on leaves remains (Table 1). The radiocarbon date obtained at 157 cm downcore (ca 208 BC) confirmed that the turbidite observed at 163e166 cm depth is related to the large pre-historic earthquake that occurred in Central Switzerland ca 2200 years ago (Strasser et al, 2006) (Fig. 2A).…”
Section: Chronostratigraphymentioning
confidence: 48%
“…The age model for the lower part of the core was constrained using two radiocarbon dates published in Thevenon and Anselmetti (2007), and two new radiocarbon dates (ETH-37378 and ETH-37379) also carried out on leaves remains (Table 1). The radiocarbon date obtained at 157 cm downcore (ca 208 BC) confirmed that the turbidite observed at 163e166 cm depth is related to the large pre-historic earthquake that occurred in Central Switzerland ca 2200 years ago (Strasser et al, 2006) (Fig. 2A).…”
Section: Chronostratigraphymentioning
confidence: 48%
“…Advanced geotechnical characterization of the initial deposits, namely the checking of criteria for slope failure (Stegmann et al, 2007;Strasser et al, 2006), might help in defining the energy associated to the local seismic events.…”
Section: Relationship Between "Homogenites" and Co-seismic Faults Offmentioning
confidence: 99%
“…For the subaqueous records, two major groups of effects can be detected and analyzed: (i) in situ post-depositional disturbances (e.g., Sims, 1975;Marco and Agnon, 1995;Ken-Tor et al, 2001;Rodriguez-Pascua et al, 2002, and (ii) gravity-driven reworking and resettling of large masses of unconsolidated sediments (e.g., Adams, 1990;Strasser et al, 2006). Two major questions arise for both groups: (1) how to ensure the earthquake-triggering, (2) how to identify the responsible active structure(s).…”
Section: Introductionmentioning
confidence: 99%